2016
DOI: 10.5301/ijao.5000538
|View full text |Cite
|
Sign up to set email alerts
|

International Coordinator Survey Results on the Outpatient Management of Patients with the Heartware® Ventricular Assist System

Abstract: This survey showed specific differences in outpatient management strategies that were previously unreported. However, further studies with correlations to patient outcomes are necessary to determine optimal patient management recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…Currently, only 25.7% of VAD centers require their patients to measure blood pressure at home. 16 The results of this study are a step toward a system to measure blood pressure noninvasively in out-of-hospital RBP recipients even in the case of low pulsatility and/or arrhythmic events. This would have a great benefit for the monitoring and subsequently the treatment of this patient population.…”
Section: Discussionmentioning
confidence: 87%
“…Currently, only 25.7% of VAD centers require their patients to measure blood pressure at home. 16 The results of this study are a step toward a system to measure blood pressure noninvasively in out-of-hospital RBP recipients even in the case of low pulsatility and/or arrhythmic events. This would have a great benefit for the monitoring and subsequently the treatment of this patient population.…”
Section: Discussionmentioning
confidence: 87%
“…The periodic alternation between open and closed conditions will allow gradual training of heart muscle and thus reduce the risk of aortic atrophy. In the future, this can be used to establish methods for myocardial recovery [32, 33] as there is a need for advanced control strategies and consistent outpatient management [34].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible contribution to improved survival in the TI group is better adherence to institutional guidelines for anticoagulation and hypertension management: Previous studies revealed that VAD patients spent only 50–60% of their TTR and only 11.4% of patients transmit their INR readings telemetrically to the VAD center , suggesting room for improvement. In this study, patients in the TI cohort reported a mean INR of 2.4 ± 0.4 and spent 72.2% of the TTR, possibly contributing to the reduced readmission rates based on major bleeding of 20.8% (TI) versus 36.4% in the UC group.…”
Section: Discussionmentioning
confidence: 99%